Struktur Kalimat Tunggal dalam Buku Cerita Anak ‘Kisah Petualangan Seru Kancil dan Teman-Temannya’: Analisis Fungsi, Kategori, dan Peran Sintaksis - Anggraeni, Eliesa Ratih (Research Community for Critical Society and Environment, 2026)
This research is a syntactic study in a children's storybook titled Kisah Petualangan Seru Kancil dan Teman-temannya (The Exciting Adventure Story of the Mouse Deer and His Friends). The aim of this research is to analyze the functions, categories, and syntactic roles in simple sentences found in the narrative of the children's book. The data were analyzed using a qualitative descriptive method with a syntactic approach, involving 21 simple sentences found in the storybook, which were classified based on the sentence structure patterns of Subject-Predicate-Object (SPO), Subject-Predicate-Adverbial (SPA), and Subject-Predicate-Object-Adverbial (SPOA). The analysis results show that these patterns reflect a simple structure that is effective in conveying the story to children. The functions, categories, and syntactic roles in each sentence also reflect consistency in the use of simple sentence patterns that are easy for children to understand through the children's storybook.